2018
DOI: 10.1080/15384101.2017.1403684
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-β4 is a novel transcriptional target of TAp73

Abstract: As a member of p53 family, p73 has attracted intense investigations due to its structural and functional similarities to p53. Among more than ten p73 variants, the transactivation (TA) domain-containing isoform TAp73 is the one that imitates the p53's behavior most. TAp73 induces apoptosis and cell cycle arrest, which endows it the capacity of tumour suppression. Also, it can exert diverse biological influences on cells through activating a complex and context dependent transcriptional programme. The transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 78 publications
2
15
0
Order By: Relevance
“…Gene Ontology (GO) enrichment (maximum false discovery rate [FDR < 2.22 × 10 −16 ]) identified nine GO categories related to biological adhesion, including extracellular matrix organization, positive regulation of cell adhesion, cell-substrate adhesion, positive regulation of locomotion, extracellular structure organization, positive regulation of cellular component movement, and positive regulation of cell motility ( Figure 5 B; Table S2 ). These findings are consistent with previous reports of p73-mediated regulation of cell-cell adhesion and migration through integrin-β4 ( Xie et al., 2018 ), vascular endothelial growth factor , and transforming growth factor β signaling ( Fernandez-Alonso et al., 2015 , Martin-Lopez et al., 2017 , Bae et al., 2018 ).
Figure 5 p73 Regulates a Gene Network Involved in Biological Adhesions in Antral Follicles (A) Principal component analysis (PCA) plot of RNA sequencing (RNA-seq) analysis from LCM-isolated p73+/+ and p73−/− antral follicles (n = 3 mice/genotype).
…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Gene Ontology (GO) enrichment (maximum false discovery rate [FDR < 2.22 × 10 −16 ]) identified nine GO categories related to biological adhesion, including extracellular matrix organization, positive regulation of cell adhesion, cell-substrate adhesion, positive regulation of locomotion, extracellular structure organization, positive regulation of cellular component movement, and positive regulation of cell motility ( Figure 5 B; Table S2 ). These findings are consistent with previous reports of p73-mediated regulation of cell-cell adhesion and migration through integrin-β4 ( Xie et al., 2018 ), vascular endothelial growth factor , and transforming growth factor β signaling ( Fernandez-Alonso et al., 2015 , Martin-Lopez et al., 2017 , Bae et al., 2018 ).
Figure 5 p73 Regulates a Gene Network Involved in Biological Adhesions in Antral Follicles (A) Principal component analysis (PCA) plot of RNA sequencing (RNA-seq) analysis from LCM-isolated p73+/+ and p73−/− antral follicles (n = 3 mice/genotype).
…”
Section: Resultssupporting
confidence: 93%
“…Motif analysis showed strong enrichment for the p53 family binding motif ( Figure S7 C) ( Rosenbluth et al., 2008 , el-Deiry et al., 1992 , Lokshin et al., 2007 , Smeenk et al., 2008 ). We identified known binding sites in p73 target genes MDM2 and CDKN1A ( Figures S7 D and S7E) ( Barak et al., 1993 , Juven et al., 1993 , Espinosa and Emerson, 2001 ) ( Robinson et al., 2011 , Thorvaldsdottir et al., 2013 ) as well as a binding site in the newly reported p73 target gene ITGB4 (integrin-β4) ( Xie et al., 2018 ). Since we were comparing murine gene expression data with human ChIP data, we focused our analysis on genes that were increased after p73 expression in MGCS and for which the binding of p73 occurred within 25 kb of the TSS in HCC1806 ChIP.…”
Section: Resultsmentioning
confidence: 91%
“…Subsequently, Fan et al [ 18 ] also showed ZFAS1 expression was down-regulated in breast cancer cell lines, and acted as a tumor suppressor in breast cancer. However, ZFAS1 has been suggested to be overexpressed in most types of human cancers such as lung cancer [ 19 ], hepatocellular carcinoma [ 20 ], osteosarcoma [ 21 ], glioma [ 22 , 23 ], colorectal cancer [ 24–26 ], gastric cancer [ 27–29 ], esophageal squamous cell carcinoma [ 30 ], ovarian cancer [ 31 ], prostate cancer [ 32 ], and acute myeloid leukemia [ 33 ]. However, the expression status of ZFAS1 in bladder cancer was still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In glioma patients, ZFAS1 overexpression was obviously correlated with advanced tumor grade [ 22 ]. Moreover, Fang et al [ 17 ], Xie et al [ 24 ], and Wang and Xing [ 25 ] consistently reported high-expression ZFAS1 was strikingly correlated with advanced clinical stage, lymph node metastasis, and vascular invasion in colorectal cancer patients. In gastric cancer, Nie et al [ 15 ] revealed that ZFAS1 high-expression in tumor tissue was correlated with large tumor size and advanced pathological stage.…”
Section: Discussionmentioning
confidence: 99%
“…Part of p63 function is also mediated by its contribution on the cellular metabolism [45,[51][52][53][54][55]. TAp73 plays a peculiar function in brain development [56][57][58] and TAp73 knockout mice exhibit significant neurodevelopmental defects, including hippocampal dysgenesis with truncation of the lower blade of the dentate gyrus [4,[59][60][61]. Concurrent loss of TAp73 and the shorter isoform ΔNp73 results in even more severe neurological phenotype; p73 full KO mice, in addition to defective hippocampus, display reduced cortical thickness and hydrocephalus [62].…”
Section: Introductionmentioning
confidence: 99%